2022
DOI: 10.3390/foods11141993
|View full text |Cite
|
Sign up to set email alerts
|

Using Rosemary Essential Oil as a Potential Natural Preservative during Stirred-like Yogurt Making

Abstract: The popularity of rosemary has grown as a natural alternative over the synthetic supplements due to its potential health benefits. The rosemary plant has been utilized to preserve food due to its ability to prevent oxidation and microbial contamination. The reason for this study was to determine the phytochemical components and antimicrobial activity of rosemary essential oil (REO) and the effect of REO addition (0.5 and 0.7%) on the chemical, microbiological, and sensory properties of stirred-like yogurt (SLY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…The desorption process was endothermic as indicated by the minimum of 108.5 °C on the DSC curve (Figure 13). The FTIR for evolved gases indicated the presence of borneol at 107 °C, quickly followed by α-caryophyllene at 112 °C [75]. The complete oxidation of remaining organic molecules occurred between 225 and 500 °C when a mass loss of 1.76% was recorded, accompanied by a strong exothermic effect at 338.2 °C.…”
Section: Thermal Analysis (Tg-dsc)mentioning
confidence: 98%
See 1 more Smart Citation
“…The desorption process was endothermic as indicated by the minimum of 108.5 °C on the DSC curve (Figure 13). The FTIR for evolved gases indicated the presence of borneol at 107 °C, quickly followed by α-caryophyllene at 112 °C [75]. The complete oxidation of remaining organic molecules occurred between 225 and 500 °C when a mass loss of 1.76% was recorded, accompanied by a strong exothermic effect at 338.2 °C.…”
Section: Thermal Analysis (Tg-dsc)mentioning
confidence: 98%
“…For the sample with rosemary essential oil, a mass loss of 2.26% was recorded up to 225 • C. The desorption process was endothermic as indicated by the minimum of 108.5 • C on the DSC curve (Figure 13). The FTIR for evolved gases indicated the presence of borneol at 107 • C, quickly followed by α-caryophyllene at 112 • C [75]. The complete oxidation of remaining organic molecules occurred between 225 and 500 • C when a mass loss of 1.76% was recorded, accompanied by a strong exothermic effect at 338.2 • C. The residual mass of 95.73% indicated that only a fraction of rosemary essential oil had been loaded on ZnO NPs, estimated at 2.77%.…”
Section: Thermal Analysis (Tg-dsc)mentioning
confidence: 99%
“…Previous studies showed that the oil extracted from rosemary can be divided into two types. In one type, the concentration of α-pinene was higher than that of 1,8cineole such as this work, [57][58][59], and in the other type, it was the opposite [60][61][62]. The highest percentage of α-pinene has been found in the essential oil of dried rosemary when compared to fresh rosemary [63].…”
Section: Gas Chromatography Resultsmentioning
confidence: 42%
“…Previous studies showed that the oil extracted from rosemary can be di vided into two types. In one type, the concentration of α-pinene was higher than that o 1,8-cineole such as this work, [57][58][59], and in the other type, it was the opposite [60-62]…”
Section: Gas Chromatography Resultsmentioning
confidence: 93%
“…The inhibition of two pathogens S. aureus and S. Typhi under the effect of REO has been found by Puvača et al [ 29 ]. Kamel et al [ 30 ] reported the antimicrobial effect of REO in two concentrations of 0.5 and 0.7% against S. aureus in stirred-like yoghurt. They attributed the potent antimicrobial activities of REO to the presence of monoterpenes such as alpha-pinene, 1,8-cineole, and borneol.…”
Section: Resultsmentioning
confidence: 99%